Analisis Kadar Ureum Pra-Hemodialisis dan Mortalitas pada Pasien Penyakit Ginjal Kronis Stadium 5 di RSUD Dr. H. Abdul Moeloek Bandar Lampung - Vira Kamalia Niswah; Ade Yonata; Ramadhana Komala; Iswandi Darwis (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Background: Chronic kidney disease (CKD) stage 5 is the final phase that requires patients to undergo hemodialysis as the main treatment. Monitoring blood urea levels before hemodialysis is an important aspect because these values can reflect the risk of death in patients. Based on this, the study aims to examine the relationship between pre-hemodialysis urea levels and mortality rates in CKD stage 5 patients at Dr. H. Abdul Moeloek Regional General Hospital in Lampung Province. Method: This study applied a quantitative observational design with a retrospective cohort approach. The data analyzed were obtained from secondary sources, namely, medical records of patients diagnosed with stage 5 CKD. The sample included 150 patients who received hemodialysis in 2023–2024, selected through consecutive sampling. Data were analyzed univariately; normality was assessed using the Shapiro-Wilk test, and bivariate analysis was conducted using the Mann-Whitney Test. Results: The mean pre-hemodialysis urea level in deceased patients was higher than in discharged patients. The Mann-Whitney test showed a significant difference in urea levels between the two groups (p=0.0001), indicating a relationship between pre-hemodialysis urea levels and patient mortality. Discussion: The findings suggest that pre-hemodialysis urea levels can serve as an indicator of mortality risk in patients with stage 5 CKD. Patients with higher urea levels tend to have a greater risk of death. Conclusion: There is a significant correlation between pre-hemodialysis urea levels and mortality in patients with stage 5 CKD. Patients with higher urea levels have a higher risk of death.